Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content: Social media marketing strategies and their impact on customer loyalty Ms. Abrar Abdullah Alazzaz Electronic Marketing and its Impact on the Corporate Entrepreneurship: A Field Study at Yemeni Private Universities in the Capital Municipality of Sana’a Asst-Prof. Ahmed Qassim Jamal Al-Deen, Mr. Ghaleb Abdullah Ghawth The Impact of the Quality of Tourism Services Provided by Small and Medium Enterprises on Tourist Satisfaction in North Al Sharqiya Governorate, Sultanate of Oman Co-Prof. Hayel Abd Elmawla Tashtoush, Ms. Yusra Amer Suleiman Al-Maskariyah, Ms. Rahma Salem Abdullah Al-Harthiyah , Ms. Jokha Salem Shannan Al-Zuwaidiyah ,Eng. Asya Yusuf Mohammed Al-Maskariyah The degree to which strategic leadership is practiced and its relationship to crisis management in the Public Broadcasting Corporation in the southern governorates Southern M. Ramzi Moh. Nader Abu Hilal The relationship between managers’ emotional intelligence and human resource management effectiveness Ms. Munirah A. S. AlGhanim The Role of Accounting Information Systems in Disclosure of Environmental Costs "A Case Study of Zawiya Oil Refining Company for the Year 2017" Co-Prof. Khaled Al-Bashir Muhammad Ahmad ,Mr. Omar Misbah Al-Mazoughi University governance challenges and opportunities in light of the Fourth Industrial Revolution Ms. Fatima A. Algazo, Ms. Zain M. Aldahabi, Dr. Amal Marshed Alanazi, Ms. Rula Yousef Hajjaj